2018
DOI: 10.1097/ncc.0000000000000608
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening in Women With Severe Mental Disorders

Abstract: Mental health nurses could be the optimum professionals to promote cancer primary and secondary prevention in women with mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…During the rehabilitation period, patients are most worried about the disease outcome and are more eager to obtain professional and authoritative information about disease treatment and rehabilitation from medical professionals. 14 , 15 The results showed that most respondents felt they needed to obtain information about treatment and rehabilitation related to the disease, and some respondents also mentioned their sexual problems. Owing to intense clinical work and insufficient attention from medical staff, patient health education has become a mere formality, and there is a particular lack of sexual guidance.…”
Section: Discussionmentioning
confidence: 99%
“…During the rehabilitation period, patients are most worried about the disease outcome and are more eager to obtain professional and authoritative information about disease treatment and rehabilitation from medical professionals. 14 , 15 The results showed that most respondents felt they needed to obtain information about treatment and rehabilitation related to the disease, and some respondents also mentioned their sexual problems. Owing to intense clinical work and insufficient attention from medical staff, patient health education has become a mere formality, and there is a particular lack of sexual guidance.…”
Section: Discussionmentioning
confidence: 99%
“…This process is relatively long and does not require hospitalization. Therefore, during the out-of-hospital treatment, it is necessary to strictly follow the doctor's advice to take drugs, at the same time, to correct the bad living habits, reasonable control of diet to regulate endocrine (Borrull-Guardeño et al, 2019;Hasanpour et al, 2017). PDCA circulation combined with the guidance of WeChat, that is, first of all, to clear the nursing process and content of out-of-hospital continuation, and develop a nursing plan in line with the treatment needs of patients.…”
Section: Discussionmentioning
confidence: 99%